CONCEPT AND PROCEDURE OF THE CONTENT ANALYSIS METHOD FOR EXPLORING INFORMATION IN THE FIELDS OF ISLAMIC RELIGIOUS EDUCATION, COMMUNICATION, SOCIAL SCIENCES, AND HUMANITIES - Norlaila; Jannatul Khair; Muhammad Rasyid (RADJA PUBLIKA, 2026)
Content analysis is one of the important research methods in the dissemination of information and scientific innovation in the rapid development of the current and future information, communication and technology. This method is used in qualitative and quantitative research. The goal is to explore and uncover the meaning behind information in various written, oral, and digital media as well as multi-visual and multi-lingual. This method can be used to conduct studies in various disciplines, such as education, communication, religion, social, humanities and political science as well as other fields. This article comprehensively discusses the concept, objectives, urgency, and procedures related to the implementation of content analysis, accompanied by an illustration of its application with examples conducted in research in the field of Islamic Religious Education. The discussion of this article is carried out using literature review techniques. Data collection and analysis include editing, organiting and finding references that are analyzed as research data, using the flow of library review analysis. The description of research results related to content analysis is expected to provide an understanding of the concept, objectives and urgency as well as the procedure for applying the type of content analysis research method. In addition, it is expected to encourage researchers to conduct research in the field of Islamic Religious Education and various other scientific fields with content analysis.